2022
DOI: 10.17323/jle.2022.11157
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Written Summarizing Strategy Training and Reading Comprehension: Peer-Mediated vs. Individualistic Task Performance

Abstract: Background: Drawing upon Socio-Cultural Theory (SCT), this study inspected the impact of spoken and written summary training on intermediate EFL students’ long-term reading comprehension in individual and peer-mediated conditions. Method: 120 Iranian EFL intermediate male and female learners aged 16 to 18 years were randomly assigned into two main conditions (i.e., individual and peer-mediated). Moreover, each condition was divided into spoken, written, and no summary groups. The treatment lasted for six sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In contrast, other studies revealed that learners in the collaborative learning mode outperformed the individual learning on comprehension and recall of main ideas (Osa-Melero, 2012), reading comprehension and motivation (C. Y. Pan & Wu, 2013), reading comprehension and incidental vocabulary (Teng & Reynolds, 2019), and reading comprehension (Aghazadeh et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, other studies revealed that learners in the collaborative learning mode outperformed the individual learning on comprehension and recall of main ideas (Osa-Melero, 2012), reading comprehension and motivation (C. Y. Pan & Wu, 2013), reading comprehension and incidental vocabulary (Teng & Reynolds, 2019), and reading comprehension (Aghazadeh et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…In the summarizing phase, each student had the opportunity to share their meaning with their peers and their teacher and was in an interactive process. In some studies in the literature, it has been seen that summarizing strategies are a practical approach to reading processes and support reading skills (Solikhah, & Sari, 2022;Triana, 2021;Zahra et al, 2022). While the students were using the trial module, the environment was active between 28 and 47 minutes.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 99%